Generalized trust as a foundation for online trust: findings from Austria, Greece, Poland, the Philippines, and South Africa - Markus Hadler; Boštjan Vrečar; Rebecca Schaffer (Frontiers in Sociology)
In this paper, we examine the relationship between generalized trust and online trust to assess whether the latter is a distinct phenomenon or an extension of the former. For this purpose, we provide an overview of different approaches developed to explain trust and discuss their applicability to online trust. Our analysis is based on a nationally representative sample of Austrians aged 16 or older, collected as part of the latest International Social Survey Programme (ISSP) survey on “Digital Societies,” as well as pretest data for this survey from Austria, Greece, Poland, the Philippines, and South Africa. Regression models considering indicators associated with a wide range of different approaches show that generalized trust is the strongest predictor of online trust. Hence, our findings suggest that online trust is not an independent concept but an extension of generalized trust, supporting the initial notion of generalized trust as a concept that goes beyond personal relationships, now also into the digital world.